Complex intervention based on protective factors to improve resilience for gastric cancer patients: Mixed-methods process evaluation protocol - Xia Zhao; Min Fan; Yanan Ding; Yuqin Pan; Xinqiong Zhang (PLoS ONE, 2025)
Background Gastric cancer represents a global health burden, with patients often experiencing significant psychological distress due to various treatments. Resilience, the ability to adapt positively to challenges, is crucial for the mental and physical well-being of gastric cancer patients. Despite its importance, there are still gaps in research aimed at enhancing resilience. This paper presents a process evaluation protocol embedded within a complex intervention aimed at enhancing resilience in gastric cancer patients during chemotherapy. The protocol aims to understand the implementation process, mechanisms, influencing factors, and outcomes. Methods The process evaluation will use a mixed-methods approach. The Consolidated Framework for Implementation Research (CFIR) and the RE-AIM framework were chosen to qualitatively identify the factors that influence intervention implementation and the outcomes of implementation, including the reach, efficacy, adoption and maintenance. The implementation process will be assessed based on the UK Medical Research Council’s guidance on evaluating complex interventions. The fidelity, dose and adherence will be analysed through the goal achievement log book, and the mechanisms of intervention implementation will be assessed using parallel latent growth curve model with quantitative information. Semi-structured interviews will be conducted with intervention staff and participants, data from the goal achievement log book will be analyzed, and data from the primary and secondary outcome indicators will be analyzed for parallel latent growth curve parameters. Discussion This study outlines a process evaluation protocol for a complex intervention. The protocol aims to further validate the effectiveness of the intervention and guide the development of more comprehensive resilience strategies, thus promoting broader application among other chronic disease patient populations. Trial registration The trial has been prospectively registered on 11 July 2023; ChiCTR2300073466.